Taking control: Which taxes could be devolved to English local government? - Neil Amin-Smith; Tom Harris; David Philipps (Institute for Fiscal Studies (IFS), 2019)
In recent years, there has been renewed interest in the question of whether additional taxes should be devolved to English local government. The past decade has seen a number of changes to how local government is funded, including the introduction of business rates retention. Broadly, these changes have focused on giving councils more control over their funding and providing stronger financial incentives to councils to drive local growth and development. Devolution of additional tax revenues and powers could be seen as a natural extension of this agenda. After years of cuts, councils in England face serious short-term funding pressures. In the longer term the costs of funding social care are likely to increase faster than the revenues councils receive from council tax and business rates. While these issues could be addressed by using national taxation to increase the grant-funding given to councils, devolution of additional tax revenues and powers could also play a role. This report: looks at the taxes currently devolved to local government in England and in other countries; sets out criteria which can be used to assess whether different taxes and tax powers are in fact suitable for devolution; applies these to a range of taxes; and looks at how much could be raised in different parts of England from different options.
Keywords: 330